High-strength and high-toughness aluminum-lithium alloy material and preparation method thereof
By increasing the Li content and adding microalloy elements such as Zn and Zr, the microstructure of aluminum-lithium alloys is optimized, and the existing aluminum-lithium alloys have been solved, and the combination of high strength, high toughness and low density is achieved.
Patent Information
- Application Number
- CN202411779922.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-04-04
AI Technical Summary
The existing aluminum-lithium alloy materials with high Cu and low Li have high density and low weight reduction effect, making it difficult to have both high strength, high toughness and low density.
By increasing the Li content to 1.8% to 2.5%, combined with the addition of microalloy elements such as Zn and Zr, the microstructure and phase composition of the alloy are optimized, and the strength and density of the alloy are reduced.
The low density and high modulus of alloy materials are achieved, the ultimate tensile strength reaches more than 550MPa, the yield strength is more than 500MPa, the elongation is higher than 8%, and the L-T direction KⅠc can reach more than 32MPam1/2.
Smart Images

Figure CN119753462A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a high-strength and high-toughness aluminum-lithium alloy material and a preparation method thereof, and belongs to the field of metal material engineering. Background Art
[0002] Aluminum-lithium alloys containing basic alloying elements Cu and Li are gradually being widely used in the field of aviation manufacturing due to their excellent strength / toughness / fatigue / corrosion resistance. With the development of aluminum-lithium alloy metallurgical technology, the metallurgical development trend of aluminum alloys is high purity, high alloying and micro-alloying, thereby obtaining excellent comprehensive performance. The metallurgical development achievements of Al-Cu-Li-X series aluminum-lithium alloys are mainly: 1) Controlling the content of Fe and Si impurity elements; 2) Adding micro-alloying elements such as Ag, Zn, and Mg to coordinate the precipitation process of the second strengthening phase, optimize the toughness and stress corrosion resistance; 3) Adding micro-alloying elements such as Mn, Zr, and Sc to control the material structure and improve the comprehensive toughness and damage resistance. The Al-Cu-Li-X series aluminum-lithium alloys currently used in aviation are mainly 2198, 2196, 2297, 2397, 2099, 2060, 2050, etc.
[0003] In the past 30 years, the focus has been on the development of new aluminum-lithium alloys with high Cu and low Li, with Li content below 2.0wt%, high Cu / Li ratio, and strict control of impurity elements Fe and Si content. These alloys have high Cu content, ensuring high strength. However, the low Li content makes the alloy density higher, and the weight reduction effect is low. Summary of the invention
[0004] The present invention is designed to provide a high-strength and high-toughness aluminum-lithium alloy material and a preparation method thereof in response to the above-mentioned existing technical conditions. The purpose is to make the alloy material have low density, high modulus, and both high strength and high toughness. The specific index requirements are that the ultimate tensile strength should be above 550MPa, the yield strength should be above 500MPa, and the elongation should be higher than 8%, and the LT to K Ⅰc Up to 32MPam 1 / 2 Above; density ρ≤2.65g / cm 3 , elastic modulus E≥80GPa, meeting the above requirements, the alloy material products described in the technical solution of the present invention can be used as structural elements in the fields of aerospace, nuclear industry, transportation, sporting goods, weapons, etc.
[0005] The objective of the present invention is achieved through the following technical solutions:
[0006] The high-strength and high-toughness aluminum-lithium alloy material proposed in the technical solution of the present invention comprises the following chemical components and weight percentages: Cu 2.8% to 4.0%, Li 1.8% to 2.5%, Zn 0.40% to 0.80%, Zr 0.06% to 0.15%, impurity Si ≤ 0.12%, impurity Fe ≤ 0.15%, other impurities each ≤ 0.05%, the total amount of other impurities ≤ 0.15%, and the balance is Al.
[0007] In addition, the alloy material further comprises one or more of Mn, Mg, Ag and Sc, and the weight percentages of the above four alloy elements are as follows: Mg 0.30% to 1.1%, Mn 0.20% to 0.60%, Ag 0.20% to 0.80%, Sc 0.06% to 0.40%.
[0008] The alloy material of the present invention is designed with a relatively high Li content, with the highest Li element weight percentage reaching 2.50%. The increase in the Li element content results in a lower alloy density and a higher elastic modulus, while also bringing about an improvement in the overall strength and toughness properties.
[0009] In addition, the alloy material of the present invention adds Zn element with a weight percentage content of up to 0.80%. Zn element has solid solution strengthening and aging strengthening effects, can promote the precipitation of δ' phase, and reduce its coarsening and growth rate. Zn element can also promote the precipitation of S' and T1 phases, thereby improving the strength and plasticity of the alloy; Zn element also has another effect equivalent to Ag element, that is, improving the corrosion performance of the alloy, increasing the exfoliation corrosion and stress corrosion resistance of the alloy material, the reason is that Zn element promotes the precipitation of Cu-rich phase from the matrix, reducing The supersaturation of Cu in the matrix is reduced, so that the local micro-potential difference is reduced; Zn can dissolve into the coarse T1 phase at the grain boundary, and may also dissolve into the T1 phase in the subgrain boundary and the matrix. The dissolution of Zn will affect the electrochemical properties of the T1 phase; at the same time, Zn has an indirect effect on the precipitation kinetics of the alloy, and the changes in the size and volume fraction of the precipitated phase affect the local stress corrosion performance; the Zn element also has an important role, that is, entering the intergranular (A1CuFe) and forming a complex low-melting impurity phase during casting, which can reduce the number and size of micro-porosity. Therefore, in general, the addition of Zn element to the alloy material of the present invention can improve the alloy's strength and plasticity, corrosion resistance and metallurgical quality;
[0010] In addition, the alloy material of the present invention adds a Zr element with a weight percentage content of up to 0.15%. When the Zr element is added to the aluminum alloy, a dispersed phase such as Al3Zr will be formed, which is coherent with the Al matrix and can serve as a recrystallization nucleation position, thereby inhibiting the size of the recrystallized grains and improving the toughness. Therefore, in general, the addition of the Zr element to the alloy material of the present invention can improve the toughness of the alloy.
[0011] Therefore, the alloy material of the present invention has the characteristics of high Li content, lower alloy density, higher elastic modulus, and better comprehensive strength and toughness properties.
[0012] In one embodiment, the alloy material comprises the following chemical components and weight percentages: Cu 3.0% to 3.8%, Li 2.05% to 2.35%, Zn 0.40% to 0.80%, Zr 0.08% to 0.15%, impurity Si ≤ 0.12%, impurity Fe ≤ 0.15%, other impurities each ≤ 0.05%, the total amount of other impurities ≤ 0.15%, and the balance is Al.
[0013] In one embodiment, the alloy material comprises the following chemical components and weight percentages: Cu 3.3% to 3.8%, Li 2.0% to 2.5%, Zn 0.40% to 0.80%, Zr 0.08% to 0.15%, impurity Si ≤ 0.12%, impurity Fe ≤ 0.15%, other impurities each ≤ 0.05%, the total amount of other impurities ≤ 0.15%, and the balance is Al.
[0014] In one embodiment, the alloy material comprises the following chemical components and weight percentages: Cu 2.8% to 3.4%, Li 1.8% to 2.4%, Zn 0.45% to 0.75%, Zr 0.08% to 0.15%, Mg 0.30% to 1.1%, Mn 0.20% to 0.60%, Ag 0.20% to 0.80%, Sc 0.06% to 0.40%, impurity Si ≤ 0.08%, impurity Fe ≤ 0.12%, other impurities each ≤ 0.05%, the total amount of other impurities ≤ 0.15%, and the balance is Al.
[0015] The technical solution of the present invention also provides a method for preparing the above-mentioned high-strength and high-toughness aluminum-lithium alloy material, which is characterized in that the steps of the method are as follows:
[0016] Step 1: pre-batch the materials according to the composition ratio of the alloy materials, wherein the pre-batch does not contain metallic Li raw materials;
[0017] Step 2: Melting the pre-batch in a melting furnace at a melting temperature of 680°C to 780°C;
[0018] Step 3, refining the completely molten metal liquid, and maintaining the metal temperature in the range of 700°C to 760°C during refining;
[0019] Step 4: The refined molten metal is transferred to a vacuum standing furnace, and the metal Li raw material is added, and the molten metal is allowed to stand in a vacuum state, with a vacuum degree of 1000Pa to 1300Pa. The vacuum standing process is divided into the following four steps:
[0020] Step 1: Heat to 760°C and keep warm for at least 3 minutes;
[0021] Step 2: Heat to 790°C and keep warm for no less than 10 minutes;
[0022] Step 3: Cool down to 760℃ and keep warm for no less than 4 minutes;
[0023] Step 4: Cool down to 720℃ and keep warm for no less than 3 minutes;
[0024] Step 5: After the standing is completed, argon gas protection casting is started, the furnace mouth temperature is maintained in the range of 700℃~720℃, and the casting speed is 15~200mm / min;
[0025] Step 6: Perform a two-stage homogenization treatment on the alloy ingot in a heating furnace, wherein the first-stage homogenization temperature is 400°C to 420°C, the second-stage homogenization temperature is 480°C to 510°C, and the second-stage homogenization time is not less than 36 hours;
[0026] Step 7: After the homogenized ingot is peeled, high-temperature processing is performed. During the high-temperature processing, the billet should be kept in a temperature range of 380°C to 480°C. The high-temperature processing and forming methods include the following:
[0027] After the homogenized ingot is peeled, hot extrusion is performed. During the hot extrusion process, the billet should be kept in the temperature range of 380℃~440℃;
[0028] After the homogenized ingot is peeled, hot forging is performed. During the forging process, the billet should be kept in the temperature range of 380℃~470℃;
[0029] After the homogenized ingot is peeled, it is hot-ring rolled into a cylindrical piece. During the hot-ring rolling process, the billet should be kept in the temperature range of 380℃~470℃;
[0030] Step 8: heat-treat the formed blank to obtain excellent comprehensive properties, and then manufacture parts through drawing, bending, rolling and milling;
[0031] The heat treatment system is: 520°C solid solution, room temperature water quenching and cooling to room temperature, 1.0% to 9.0% permanent cold deformation pre-stretching, 140°C / 8 to 60h aging treatment.
[0032] The above preparation method can make the high-strength and high-toughness aluminum-lithium alloy material into a plate with a thickness of up to 80 mm. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 It is a schematic diagram of the melting and casting process when preparing alloy materials in the technical solution of the present invention. DETAILED DESCRIPTION
[0034] The technical solution of the present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments:
[0035] The chemical composition and weight percentage of the alloy material selected in this embodiment are shown in Table 1.
[0036] When preparing the alloy material, Figure 1 The schematic diagram of the ingot melting and casting process shown in the figure shows that the raw materials are melted in a master alloy melting furnace, and then the refined molten metal is transferred into a vacuum standing furnace for vacuum standing. After standing, the molten metal enters the crystallizer through the flow channel, argon protection filter flow control system, and pipeline flow port under the protection of argon throughout the process to complete the casting.
[0037] The specific steps of the preparation process are as follows:
[0038] Step 1: pre-batch the materials according to the composition ratio of the alloy materials, wherein the pre-batch does not contain metallic Li raw materials;
[0039] Step 2: Melting the pre-batch in a melting furnace at a melting temperature of 680°C to 780°C;
[0040] Step 3, refining the completely molten metal liquid, and maintaining the metal temperature in the range of 700°C to 760°C during refining;
[0041] Step 4: The refined molten metal is transferred to a vacuum standing furnace, and the metal Li raw material is added, and the molten metal is allowed to stand in a vacuum state, with a vacuum degree of 1000Pa to 1300Pa. The vacuum standing process is divided into the following four steps:
[0042] Step 1: Heat to 760°C and keep warm for at least 3 minutes;
[0043] Step 2: Heat to 790°C and keep warm for no less than 10 minutes;
[0044] Step 3: Cool down to 760℃ and keep warm for no less than 4 minutes;
[0045] Step 4: Cool down to 720℃ and keep warm for no less than 3 minutes;
[0046] Step 5: After the standing is completed, argon gas protection casting is started, the furnace temperature is maintained in the range of 700°C to 720°C, the casting speed is 15 to 200 mm / min, and a 200×600 mm square ingot is cast;
[0047] Step 6: Perform a two-stage homogenization treatment on the alloy ingot in a heating furnace, wherein the first-stage homogenization temperature is 400°C to 420°C, the second-stage homogenization temperature is 480°C to 510°C, and the second-stage homogenization time is not less than 36 hours;
[0048] Step 7. In this embodiment, after the homogenized ingot is peeled, high-temperature rolling is performed. During the high-temperature rolling process, the billet should be kept in a temperature range of 380° C. to 480° C., and a plate having a size of 80 mm thickness × 600 mm width × 2000 mm length is rolled out;
[0049] Step 8: heat-treat the formed blank to obtain excellent comprehensive properties, and then manufacture parts through drawing, bending, rolling and milling;
[0050] The heat treatment system is: 520°C solid solution, room temperature water quenching and cooling to room temperature, 1.0% to 9.0% permanent cold deformation pre-stretching, 140°C / 8 to 60h aging treatment.
[0051] The properties of the thick plate finally obtained are shown in Table 2. It can be seen that the alloy material prepared by the present invention has excellent strength and fracture toughness, the ultimate tensile strength can reach more than 550MPa, the yield strength is more than 500MPa, and the elongation is higher than 8%, and the LT to K Ⅰc Up to 32MPam 1 / 2 Above; density ρ≤2.65g / cm 3 , elastic modulus E≥80GPa. The products made of this material can be used as structural components in the fields of aerospace, nuclear industry, transportation, sports goods, weapons, etc.
[0052] Table 1 Alloy composition
[0053]
[0054]
[0055] Table 2 Thick plate properties
[0056]
Claims
1. A high-strength and high-toughness aluminum-lithium alloy material, characterized in that: The alloy material comprises the following chemical components and weight percentages: Cu 2.8% to 4.0%, Li 1.8% to 2.5%, Zn 0.40% to 0.80%, Zr 0.06% to 0.15%, impurity Si ≤ 0.12%, impurity Fe ≤ 0.15%, each of other impurities ≤ 0.05%, the total amount of other impurities ≤ 0.15%, and the balance is Al.
2. The high-strength and high-toughness aluminum-lithium alloy material according to claim 1, characterized in that: The alloy material further comprises one or more of Mn, Mg, Ag and Sc, wherein the weight percentages of the above four alloy elements are as follows: Mg 0.30% to 1.1%, Mn 0.20% to 0.60%, Ag 0.20% to 0.80% and Sc 0.06% to 0.40%.
3. The high-strength and high-toughness aluminum-lithium alloy material according to claim 1, characterized in that: The alloy material comprises the following chemical components and weight percentages: Cu 3.0% to 3.8%, Li 2.05% to 2.35%, Zn 0.40% to 0.80%, Zr 0.08% to 0.15%, impurity Si ≤ 0.12%, impurity Fe ≤ 0.15%, each of other impurities ≤ 0.05%, the total amount of other impurities ≤ 0.15%, and the balance is Al.
4. The high-strength and high-toughness aluminum-lithium alloy material according to claim 1, characterized in that: The alloy material comprises the following chemical components and weight percentages: Cu 3.3% to 3.8%, Li 2.0% to 2.5%, Zn 0.40% to 0.80%, Zr 0.08% to 0.15%, impurity Si ≤ 0.12%, impurity Fe ≤ 0.15%, each of other impurities ≤ 0.05%, the total amount of other impurities ≤ 0.15%, and the balance is Al.
5. The high-strength and high-toughness aluminum-lithium alloy material according to claim 2, characterized in that: The alloy material comprises the following chemical components and weight percentages: Cu 2.8%-3.4%, Li 1.8%-2.4%, Zn 0.45%-0.75%, Zr 0.08%-0.15%, Mg 0.30%-1.1%, Mn 0.20%-0.60%, Ag 0.20%-0.80%, Sc 0.06%-0.40%, impurity Si≤0.08%, impurity Fe≤0.12%, each of other impurities≤0.05%, the total amount of other impurities≤0.15%, and the balance is Al.
6. A method for preparing the high-strength and high-toughness aluminum-lithium alloy material according to claim 1, characterized in that: The steps of this method are as follows: Step 1: pre-batch the materials according to the composition ratio of the alloy materials, wherein the pre-batch does not contain metallic Li raw materials; Step 2: Melting the pre-batch in a melting furnace at a melting temperature of 680°C to 780°C; Step 3, refining the completely molten metal liquid, and maintaining the metal temperature in the range of 700°C to 760°C during refining; Step 4: The refined molten metal is transferred to a vacuum standing furnace, and the metal Li raw material is added, and the molten metal is allowed to stand in a vacuum state, with a vacuum degree of 1000Pa to 1300Pa. The vacuum standing process is divided into the following four steps: Step 1: Heat to 760°C and keep warm for at least 3 minutes; Step 2: Heat to 790℃ and keep warm for not less than 10 minutes; Step 3: Cool down to 760℃ and keep warm for no less than 4 minutes; Step 4: Cool down to 720℃ and keep warm for no less than 3 minutes; Step 5: After the standing is completed, argon gas protection casting is started, the furnace mouth temperature is maintained in the range of 700℃~720℃, and the casting speed is 15~200mm / min; Step 6: Perform a two-stage homogenization treatment on the alloy ingot in a heating furnace, wherein the first-stage homogenization temperature is 400°C to 420°C, the second-stage homogenization temperature is 480°C to 510°C, and the second-stage homogenization time is not less than 36 hours; Step 7: After the homogenized ingot is peeled, high-temperature processing is performed to form the ingot. During the high-temperature processing, the temperature of the ingot should be kept within the range of 380°C to 480°C; Step 8: heat-treat the formed blank to obtain excellent comprehensive properties, and then manufacture parts through drawing, bending, rolling and milling; The heat treatment system is: 520°C solid solution, room temperature water quenching and cooling to room temperature, 1.0% to 9.0% permanent cold deformation pre-stretching, 140°C / 8 to 60h aging treatment.
7. The method for preparing a high-strength and high-toughness aluminum-lithium alloy material according to claim 6, characterized in that: In the step 7, the homogenized ingot is peeled and then hot extruded. During the hot extrusion process, the billet should be kept in a temperature range of 380° C. to 440° C.
8. The method for preparing a high-strength and high-toughness aluminum-lithium alloy material according to claim 6, characterized in that: In the step 7, the homogenized ingot is peeled and then hot forged. During the forging process, the billet should be kept in a temperature range of 380° C. to 470° C.
9. The method for preparing a high-strength and high-toughness aluminum-lithium alloy material according to claim 6, characterized in that: In the step 7, the homogenized ingot is peeled and then hot ring rolled into a cylindrical piece. During the hot ring rolling process, the billet should be kept in a temperature range of 380° C. to 470° C.